تشخيص واقع استخدام التصور الذهني أثناء الإعداد الخططي في كرة القدم - مخلوفي, بومدين; حمزاوي, حكيم; بارودي, محمدأمين (جامعة الوادي - University of Eloued, 2023)
هدف البحث إلى تشخيص واقع استخدام التصور الذهني أثناء الإعداد الخططي للاعبي كرة القدم، واستخدم الباحث المنهج الوصفي بالدراسة المسحية، وشملت عينة البحث (86) مدربا، وطبق الباحث استبيان يتكون من محورين (الجانب المعرفي العام للتصور الذهني، الجانب التطبيقي للتصور الذهني). وتوصلت نتائج البحث إلى آن أغلبية المدربين ليس لهم معرفة كافية للتصور الذهني ولا يستخدمونه أثناء الإعداد الخططي للاعبين وأوصى الباحث ب ضرورة إخضاع المدربين لدورات تكوينية نظرية وتطبيقية في التحضير النفسي والعقلي، وضرورة استخدام التصور الذهني أثناء العمل الميداني في حصص التدريب والمنافسة. - الكلمات المفتاحية: (التصور الذهني، الإعداد الخططي، كرة القدم).Abstract: The research aimed to diagnose the reality of the use of mental imagery during the tactical preparation of football players, and the researcher used the descriptive approach in the survey study, and the research sample included (86) coaches. The researcher applied a questionnaire consisting of two axes (the general cognitive aspect of mental imagery, and the practical aspect of mental imagery). The results of the research concluded that the majority of coaches do not have sufficient knowledge of mental imagery and do not use it during the tactical preparation of the players The researcher recommended the need to subject the trainers to theoretical and practical training courses in psychological and mental preparation, and the need to use mental imagery during field work in training sessions and competition.
مقال
Keywords: التصور الذهني، الإعداد الخططي، كرة القدم; mental perception, tactical preparation, football